1975
DOI: 10.1111/j.1151-2916.1975.tb11482.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot‐Pressing of Silicon Carbide with 1% Boron Carbide Addition

Abstract: The densification behavior of pressure sintered cubic silicon carbide containing 1 wt% boron carbide was studied as a function of temperature (1750" to 1950°C). Specimens of theoretical density were obtained at 1950" with a pressure of 3000 psi. Experimental results showed that densification proceeded by a plastic flow mechanism. Interpretation of the data in terms of Murray's equation yields an activation energy of (115+ 18) kcal/mol. At 1850°C and above, tabular grains of 6H and 2H SIC were observed in a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Indeed, to reach fully dense SiC-based materials (without sintering additives) by using conventional pressurized techniques such as hot-pressing or hot isostatic pressing, it is well known that severe experimental conditions are required: 8,24 high sintering temperature (T ≥ 2100 • C) and high soaking time (t ≥ 30 min).…”
Section: Sps Treatment Of Pure Sicmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, to reach fully dense SiC-based materials (without sintering additives) by using conventional pressurized techniques such as hot-pressing or hot isostatic pressing, it is well known that severe experimental conditions are required: 8,24 high sintering temperature (T ≥ 2100 • C) and high soaking time (t ≥ 30 min).…”
Section: Sps Treatment Of Pure Sicmentioning
confidence: 99%
“…1,2 To achieve high densities through solid-state sintering and to avoid the appearance of low corrosion resistance intergranular phases, consolidation of silicon carbide with boron and carbon as sintering additives seems to be the most efficient way. [6][7][8][9] Therefore, boron carbide was found to enhance the hotpressing behaviour of silicon carbide that could be so obtained in a fully dense state. [10][11][12] These additives permit to reach high density slightly over 2000 • C by means of the reduction of the surface energy of the grains (boron effect) 10 and reaction with residual silica (carbon effect).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of activation energies are reported in the literature for the densification of SiC. Bind and Biggers 25 hot pressed SiC with 1 wt% B 4 C and reported an activation energy of 482±75 kJ/mol, Yang et al 26 reported values of 543–669 kJ/mol for pressureless sintering with B and C, while Hase et al 27 measured values of 837±121 kJ/mol. The 643±37 kJ/mol measured in the present study for the SiC–B–C material is within the range of values reported in the literature and is consistent with high activation energies reported for C diffusion in SiC 28 and creep 29 of this material.…”
Section: Discussionmentioning
confidence: 99%
“…The assumed densities are 3.21 g/cm 3 for SiC and 2.2 g/cm 3 for amorphous SiBCN. The theoretical density of the samples in this experiment is 3.07 g/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…To obtain high-density SiC ceramics, special sintering additives, such as B þC [2], B4C [3], and Al2O3 þY2O3 [4], are required. Several reports were recently published on the application of polymer-derived ceramics (PDCs) as a sintering aid to prepare non-oxide ceramics.…”
Section: Introductionmentioning
confidence: 99%